CORRELATION BETWEEN EMOTION REGULATION AND SPIRITUALITY WITH STRESS IN CAREGIVERS OF ELDERLY - Dwi Anjaswati Putri Hastari; Istar Yuliadi; Rini Setyowati (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2020)
Stress occurs while caring for the elderly due to several factors, namely the emotion regulation and spirituality. This study aims to examine the correlation between stress with emotion regulation and spirituality in caregivers of the elderly at Karangmojo 1 Health Center, Gunungkidul. The purposive sampling method was used to obtain data from 36 caregivers on the emotion regulation and spirituality as well as stress scale with Alpha Cronbach's reliability coefficient of 0.871, 0.921, and 0.905, respectively. The results showed that r = 0.485 and Sig. 0.012 (p <0.05). Therefore there is a correlation between stress, emotion regulation, and spirituality. This means that the higher the control of emotion and spiritual level, the lower the pressure. Furthermore, this research expects to provide input in the realm of psychology. For example, it can be used as a reference to help caregivers deal with stress by increasing their emotion regulation and spirituality skills.